PENERAPAN TEKNIK MEMBACA DALAM HATIUNTUK MENINGKATKAN KEMAMPUAN MENCARI GAGASAN POKOK KARANGAN NARASI ANAK SISWA KELAS IVSD NEGERI 012 PAGARAN TAPAH DARUSSALAM - Suriaman ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research is motivated by the lack of ability to look for the key idea of narrative essay six graders SD Negeti 012 Pagaran Tapah Darussalam. This study aims to improve the search capabilities of key ideas in the narrative essay fourth grade students of SD Negeri 012 Pagaran Tapah Darussalam through silent reading techniques, carried out for 1 month. The research subject is the fourth grade students of SD Negeri 012 Pagaran Tapah Darussalam with the number of 14 people, consisting of seven boys and seven girls. Form of research is classroom action research. The research instrument consists of instruments and instrument performance data collection activity observation sheet form teacher and student activity. Based on the research that has been done, it is obtained based on the results of the study, the research concluded that the ability to search for the key idea fourth grade students of SD Negeri 012 Pagaran Tapah Darussalam can be improved through techniques silent reading. This is evident from the increase in the student's ability in finding the key idea of prior silent reading techniques applied to the second cycle of the second meeting. Known from preliminary data the average value of students is 61.4. When viewed from the classical completeness, there are 14.3% of students (2) is completed obtaining a minimum value of 65 (according to the standard KKM), at the first meeting of the first cycle, the average grade low category (66.4). When viewed from the classical completeness, there are 50% of students (7). At the second meeting students' average score was 70.7. When viewed from the classical completeness, there are 57.1% of students (8). Thus, this research is successful. the first meeting of the second cycle, the average grade low category (74.3). When viewed from the classical completeness, there are 78.6% of students (11 people). at the second meeting of the second cycle, the average grade low category (81.4). When viewed from the classical completeness, there is 100% of students (14 people).